2021
DOI: 10.1007/s40263-021-00825-w
|View full text |Cite
|
Sign up to set email alerts
|

Viloxazine in the Management of CNS Disorders: A Historical Overview and Current Status

Abstract: Viloxazine has a long history of clinical use in Europe as an antidepressant, and has recently been repurposed into an extended-release form for the treatment of attention-deficit/hyperactivity disorder in the USA. An immediate-release formulation was approved for the treatment of depression in the UK in 1974, and was subsequently marketed there and in several European countries for 30 years with no major safety concerns. In contrast to first-generation antidepressants (e.g., tricyclic antidepressants, monoami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 72 publications
0
32
0
Order By: Relevance
“…As in prior work,9 pharmacological interventions will include stimulants (methylphenidate and amphetamines, including lisdexamphetamine); atomoxetine; guanfacine XR, clonidine, bupropion and modafinil. We will also search for eligible studies of viloxazine, which has been recently approved by the FDA for children and adolescents (aged 6–17) with ADHD 21. In the analyses, we will lump methylphenidate and amphetamines as: (1) a previous NMA9 did not find any significant difference, in terms of efficacy, between methylphenidate and amphetamines in adults with ADHD; (2) accordingly, current NICE guidelines11 recommend methylphenidate or lisdexamphetamine (or other amphetamines) as first-line pharmacological treatment for adults.…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As in prior work,9 pharmacological interventions will include stimulants (methylphenidate and amphetamines, including lisdexamphetamine); atomoxetine; guanfacine XR, clonidine, bupropion and modafinil. We will also search for eligible studies of viloxazine, which has been recently approved by the FDA for children and adolescents (aged 6–17) with ADHD 21. In the analyses, we will lump methylphenidate and amphetamines as: (1) a previous NMA9 did not find any significant difference, in terms of efficacy, between methylphenidate and amphetamines in adults with ADHD; (2) accordingly, current NICE guidelines11 recommend methylphenidate or lisdexamphetamine (or other amphetamines) as first-line pharmacological treatment for adults.…”
Section: Methods and Analysismentioning
confidence: 99%
“…We will also search for eligible studies of viloxazine, which has been recently approved by the FDA for children and adolescents (aged 6-17) with ADHD. 21 In the analyses, we will lump methylphenidate and amphetamines as: (1) a previous NMA 9 did not find any significant difference, in terms of efficacy, between methylphenidate and amphetamines in adults with ADHD; (2) accordingly, current NICE guidelines 11 recommend methylphenidate or lisdexamphetamine (or other amphetamines) as first-line pharmacological treatment for adults. Any type of nonpharmacological intervention will be considered.…”
Section: Interventionsmentioning
confidence: 99%
“…In 4 recent phase 3 trials, once‐daily viloxazine ER was well tolerated over 6 to 8 weeks of treatment (n = 1117), with a low rate of discontinuations because of adverse events (fewer than 4% across all trials). 2 , 3 , 4 , 5 , 6 , 7 In 3 of these 4 trials, statistically significant improvements in the primary end point were reported as quickly as 1 week following the onset of treatment, relative to placebo. 2 , 3 , 4 , 5 , 6 Analyses evaluating the pharmacodynamic effects of viloxazine ER within the therapeutic range have found no clear dose‐response relationship on measures of either safety or efficacy (data on file).…”
mentioning
confidence: 99%
“… 2 , 3 , 4 , 5 , 6 , 7 In 3 of these 4 trials, statistically significant improvements in the primary end point were reported as quickly as 1 week following the onset of treatment, relative to placebo. 2 , 3 , 4 , 5 , 6 Analyses evaluating the pharmacodynamic effects of viloxazine ER within the therapeutic range have found no clear dose‐response relationship on measures of either safety or efficacy (data on file). This is not surprising considering that many psychiatric treatments have demonstrated weak, if any, dose‐response relationships on a variety of outcome measures.…”
mentioning
confidence: 99%
“…In this study, viloxazine ER did not separate from placebo on the GAD-7, although viloxazine has a long history of anxiolytic properties, detailed in studies from the 1970s and 1980s when viloxazine was commonly studied as an antidepressant [ 26 , 54 57 ]. The mechanism of action also predicts not only antidepressant, but anxiolytic properties [ 26 ]. There are several plausible explanations for this negative finding.…”
Section: Discussionmentioning
confidence: 94%